TMIC-54. COMPARISON OF CELLULAR FEATURES AT AUTOPSY IN GLIOBLASTOMA PATIENTS WITH STANDARD TREATMENT OF CARE AND TUMOR TREATMENT FIELDS. (11th November 2019) - Lowman, Allison; Barrington, Alexander; Cochran, Elizabeth; Connelly, Jennifer; Mueller, Wade; LaViolette, Peter
Abstract: BACKGROUND: The FDA has approved the use of tumor treatment fields (TTFields) on patients with recurrent glioblastoma (GBM). A recent clinical trial showed that the use of TTFields along with standard treatment of care resulted in increased quality of life and survival over five years. TTFields work by delivering low intensity electric fields that disrupt GBM tumor cell division. This works to slow or even stop GBM tumor cells from dividing. METHODS: Brain tissue samples were taken from thirteen GBM patients, diagnosed at autopsy. Three patients underwent standard clinical treatment and ten patients underwent TTField therapy in addition to the standard. Tissue samples were acquired from regions where enhancement was seen on the last clinical T1 plus contrast MRI prior to death. Samples were paraffin embedded and stained with hematoxylin and eosin (H&E) and Ki67. The slides were digitized, allowing analysis of the cellular features. RESULTS: Using the H&E stained slides we compared cellular density between both groups. We found that there was not a noticeable difference in the nuclei density in areas of tumor between the groups. The percent of positive nuclei on the Ki67 stained slides was calculated and there was increased mitotically active cells per area of tissue in patients that did not undergo TTField therapy. CONCLUSION: These findings suggest there is a difference in the cellular features in areas of tumor in patients treated with TTFields compared to those with standard treatment alone. Additional research needs to be done evaluating more patients.